Traduzir o arquivo em Annie Ernaux: análise crítica e proposta de tradução de Mémoire de fille - Letícia Campos de Resende (2023)
This dissertation presents an analysis of two translations, previously published in Brazil, of two of Annie Ernaux’s most famous works (La place and Les années), as well as an original translation of Mémoire de fille (Memória de menina, better known to anglophones as A Girl’s Story), which has yet to be released in Brazil. Both the critique and the translation are based on an analytical study of Ernaux’s texts from the standpoint of their structure, language, and themes, focusing on a very specific problem: how these texts feature an individual and collective archive in a literary way. Two questions have guided our research: what are the challenges of transposing the French national archive, as mis en scène by Ernaux, into a Brazilian context? And how to effectively and practically do it? Our initial hypothesis is that both Archival Studies and Translation Studies face and have to deal with dilemmas and issues of a similar nature (the matter of origin and that of assembling and putting together material; the practice of montage), which allow us, when thinking specifically on transposing the ernausien archive, to evaluate our translation praxis. In order to take on this study, we first propose a definition of the archive. We then go on to offer a historic overview of the archive in literary texts from the eighteenth all the way to the twentieth century. Afterwards, we analyze Ernaux’s work as an example of archival literature. In the second part, we compare La place and Les années’s Brazilian translations to their French counterparts. Finally, we present our own translation of Mémoire de fille, followed by a brief critical commentary